2021
DOI: 10.1016/j.heliyon.2021.e07335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown on musculoskeletal health due to COVID-19 outbreak in Bangladesh: A cross sectional survey study

Abstract: Background During the nationwide lockdown implemented by the government of Bangladesh due to the coronavirus, has led to the various changes in the overall activities and lifestyle. Most of the people began living a sedentary lifestyle, spending more time on their phone, watching television and excessive sleeping. Reduction of physical activity level had profoundly negative impact on musculoskeletal health. Aim This study aims to investigate the impact of lockdown on mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…As indicated by our results, everyday pain was referred by signi cantly more students during the lockdown, while the percentage of asymptomatic students was signi cantly decreased, as shown by the answers in the VAS pain score. This result parallels other studies conducted during and after lockdown (Ahmed et al 2021;Roggio et al 2021), that also highlight musculoskeletal pain in numerous body locations.…”
Section: Discussionsupporting
confidence: 88%
“…As indicated by our results, everyday pain was referred by signi cantly more students during the lockdown, while the percentage of asymptomatic students was signi cantly decreased, as shown by the answers in the VAS pain score. This result parallels other studies conducted during and after lockdown (Ahmed et al 2021;Roggio et al 2021), that also highlight musculoskeletal pain in numerous body locations.…”
Section: Discussionsupporting
confidence: 88%
“…The exponential increase in sitting and its musculoskeletal sequelae during the COVID-19 pandemic enhances the relevance of this review further. Since early 2020, numerous studies have stressed that low back pain and sagittal imbalance has become quite more frequent in individuals of all ages and particularly students and young workers [15 , [47] , [48] , [49] , [50] , [51] . Oftentimes, these individuals enter a vicious circle, where they seek relief from pain in sitting, but bad sitting postures only deteriorate their pain and the underlying spinal condition [52] .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in sedentary lifestyle caused by pandemic is easily explained by the fact that spaces used for physical activity (gyms, sports clubs) have been closed due to protocols established by the government in order to minimize the spread of COVID-19 and practice PA at home is often discouraging. Ahmed et al [ 22 ] showed the lockdown has led to the various changes in the overall activities and lifestyle and the reduction of physical activity level had profoundly negative impact on musculoskeletal health. Therefore, social isolation, an important measure used by governments to inhibit the spread of SARS-COV-2, has further increased the rates of sedentary lifestyle, which is an aggravating factor for COVID-19, as its negative effects lead to increased stress, anxiety, depression and even immune depression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%